Key technology of network self-organization in 5G ultra-dense scenario - Yiming LIU; Xi LI; Hong JI (Dianxin kexue)
The ultra dense deployment and the coexistence of multi-system networks make the fifth generation（5G） mobile communications ultra-dense network operation complexity and cost increase greatly.Network self-organization has been as a key technology in 5G ultra-dense network for its excellent performance on enhancing the network management efficiency and reducing the operating costs.The network self-organization technology and its function，such as self-configuration，self-optimization and self-healing were introduced.Moreover，the technology challenges and the trends were analyzed for further research.